ANALISIS PENGARUH E-SERVICE QUALITY DAN E-WOM TERHADAP E-LOYALTY DENGAN E-SATISFACTION SEBAGAI INTERVENING PADA PENGGUNA DOMPET DIGITAL DANA - Tony Saut Parulian Sirait (Program Studi Manajemen Fakultas Ekonomi UST, 2022)
DANA is utilized by various sectors, including education, public services, social services, to street vendors. As a financial application that is of public interest, it is important for companies to prioritize the quality of e-service, e-wom, e-satisfaction, so as to increase e-loyalty of users of Dompet Digital DANA. .Satisfaction (satisfaction) is one of the factors in payments and payments related to non-cash payment systems. The quality of electronic services will influence the attitudes and behavior of someone who supports this person to become more confident in the use of an application-based technology. Word of mouth can be conveyed as information that can be accounted for and approved through online media or the internet. This study aims to determine the effect of service quality on e-satisfaction, the effect of e-wom on e-satisfaction, the effect of e-satisfaction on e-loyalty, the influence of e-service quality on e-loyalty, the effect of e-wom on e-loyalty. In this study there were 100 students of Yogyakarta City, users of DANA Digital Wallet. The data collection method uses a questionnaire method that is distributed using purposive random sampling technique. While the T test technique and classic assumptions which consist of normality test, multicollinearity test, and heterokesdasticity test. The results showed e-service variable had a positive and significant effect on e-satisfaction, e-wom had a positive and significant effect on e-satisfaction, e-satisfaction had a positive and significant effect on e-loyalty, the quality of e-service was positively and significantly related to e-loyalty, e-loyalty is positive and significant towards e-loyalty.